Effects of Biostimulants on the Chemical Composition of Essential Oil and Hydrosol of Lavandin (Lavandula x intermedia Emeric ex Loisel.) Cultivated in Tuscan-Emilian Apennines - Eleonora Truzzi; Stefania Benvenuti; Davide Bertelli; Enrico Francia; Domenico Ronga (Molecules, 2021)
In recent years, it has been shown that biostimulants can efficiently enhance plant metabolic processes, leading to an increased production of essential oil (EO) in aromatic plants. The present study aimed to evaluate the effects of two different commercial biostimulants composed of amino acids and seaweed extract, normally used for food organic crops, on the production and composition of EO and hydrosol of Lavandula x intermedia, cultivar “Grosso”. The products were applied during 2020 growing season on lavender crops in three different locations of the Northern Italian (Emilia-Romagna Region) Apennines. Plants were harvested and EOs extracted by steam distillation and analyzed by gas chromatography. Both biostimulants affected the yield of EO per plant (+11% to +49% depending on the treatment/farm combination) without significantly changing the chemical composition of EOs and hydrosols. Conversely, the composition of EOs and hydrosols are related to the location, and the main compounds of “Grosso” cultivar, limonene, 1,8-cineole, cis-ocimene, linalool, camphor, borneol, terpinen-4-ol, and linalyl acetate, show different ratios at the experimental test sites. The differences might be due to the sunlight exposure and various maintenance of the crops over the years. In conclusion, these results suggest that the employment of biostimulants on lavandin crops do not endanger the quality of the EO while increasing biomass production and promoting the sustainability of the crop.